The buyer margins of firms' exports - Jeronimo Carballo; Gianmarco I. P. Ottaviano; Christian Volpe Martincus (Goethe University Frankfurt, Center for Financial Studies (CFS), 2016)
We use detailed data on exporters from Costa Rica, Ecuador and Uruguay as well as on their buyers to show that: aggregate exports are disproportionally driven by few multi-buyers exporters; and each multi-buyer exporter's foreign sales of any product are in turn accounted for by few dominant buyers. We propose an analytically solvable multi-country model of endogenous selection in which dominant exporters, dominant products and dominant buyers emerge in parallel as multi-product sellers with heterogeneous technologies compete for buyers with heterogeneous needs. The model not only provides an explanation of the existence of dominant buyers but also makes specific predictions on how the relative importance of dominant buyers should vary across export destinations depending on their market size and accessibility. We show that these predictions are borne out by our data and discuss their welfare implications in terms of gains from trade.
urn:nbn:de:hebis:30:3-424209
Keywords: F12; F14; 330; Firm heterogeneity; taste heterogeneity; import-export relations; competition; selection